Editorial. Issue 2 (1st June 2019) - ,
Abstract : This issue of Transfers features five individual essays critically engaging with the promises promoted alongside new methods and purposes of mobility. Two essays, Martin Emanuel's "From Victim to Villain: Cycling, Traffic Policy, and Spatial Conflicts in Stockholm, circa 1980" and Andrew V. Clark and colleagues' "The Rise and Fall of the Segway: Lessons for the Social Adoption of Future Transportation, " circle around a core theme of Transfers with their fresh look at transportation, its vehicles, and its methods; two others, Noah Goodall's "More Than Trolleys: Plausible, Ethically Ambiguous Scenarios Likely to Be Encountered by Automated Vehicles" and Gal Hertz's "From Epistemology of Suspicion to Racial Profiling: Hans Gross, Mobility and Crime around 1900, " look at mobility's social side. Fascinatingly consistent are the adjectives and adverbs that qualify the promises that are made for these technologies. Segways, for instance, were sustainable, enviro-friendly, shared. Smart, personalized, and robotic are some of the commonly invoked terms in the growing literature on this particular PMD (personal mobility device). Adverbial are the benefits of automated driving too: safe and liberating, both values desired by a nineteenth-century urbanized Austrian society that imagined the city as a space of settled inhabitants free of migrants and hence also free of crimes.